Stimulation methods improvement of exit route on railway transport - Verlan, A. I. (Science and Transport Progress, 2014)
Purpose. The purpose of the article is to assess the costs, which are redistributed in the system «shipper−railroad−consignee» during routing of rail transportation and the development of tariff simulation methods of shippers to the exit routes formation. Methodology. Using economic and mathematical analysis the distribution of costs among the various participants of transportation process during the exit routes formation is investigated in the article. Findings. For implementation of the tariff simulation methods of exit routes and retention of the existing tariff structure it is proposed to provide in the «Tariff catalogue for freight transportation by railway transport of Ukraine» the discount, differentiated from haulage distance. A new method for determining the fees amount for cars supply and removal on approach tracks by train locomotives was also offered. Originality. As a result of the research a new method for determination of the exit rout efficiency that, unlike the existing one, takes into account the various interests of the individual participants in the transportation process was proposed. The dependence of the correction factors to the tariff for freight transportation in their own cars by direct exit routes from distance haulage was obtained. Implementation of these coefficients provides an approximation of railway tariffs to the traffic handling costs. A method for determination the rate of fees for cars supply and removal on approach tracks by train locomotives was offered. Practical value. InUkraine creation of the tariff discounts system for freight transportation by exit routes consistent with international practice and allows bringing the tariff to the real traffic handling cost. This change on the one hand will provide stimulation for private capital investments in infrastructure development and shunting means of approach tracks, on the other – it will fix the shippers to the railroads and stop their outflow for alternative modes of transport.